Observaciones sobre el Macá Tobiano - Erize, Francisco (1983)
Observations on the Hodded Grebe. The Hooded Grebe (Podiceps gallardoi) is a recently discovered (Rumboll, MAE April 1974), and still little known, species, belonging to the family Podicipedidae. Two trips to the site where it was discovered (April 1978 and January 1979) allowed making observations on its breeding, behavior and populations status, and organizing its conservation. The only, until then, known population, corresponding to Lake Los Escarchados (some 50 km East Southeast of Lake Argentino, Province of Santa Cruz), has been estimated in 140 to 150 individuals. It is known, though, that the number varies for these grebes migrate in winter, as the lake's surface freezes. Two additional small groups have been found in neighbouring lakes, one of them breeding (trhee pairs).